Examining the maturity of South Africa’s government departments to implement the Infrastructure Delivery Management System (IDMS) - Progress Chigangacha (University of the Free State, 2021)
The purpose of this exploratory study is to examine the maturity of South Africa’s provincial government departments in engaging with the Infrastructure Delivery Management System (IDMS) towards facilitating effective infrastructure delivery. Furthermore, the study sought to formulate evidence-based interventions that could be utilised by these government departments to engender successful delivery of infrastructure assets and associated services to their beneficiaries. This research was descriptive and employed the quantitative research approach. Data was elicited from three provincial government departments in KwaZulu-Natal, South Africa. Structured maturity modelling questionnaires were deployed for data collection from the respondents. The emergent data was analysed using the Statistical Package for the Social Sciences (SPSS), Version 26. A One-Way ANOVA, aimed at enabling a comparative analysis of differences in the degree of maturity between the three provincial government departments that utilise the IDMS, was conducted. Results from the study indicate that the three departments (cases) had a maturity rating between 3 and 4, signifying well-defined and documented standard processes that can be improved over time. However, an IDMS-ready organisation would ideally have a maturity rating at level 5. In addition, the leadership dimension was found to be a driver of all other dimensions, where a high maturity level under this dimension directly correlates with improved maturity in the other dimensions. It is recommended that adequate management and leadership support is needed to improve organisational maturity in relation to IDMS implementation. The study was confined to KwaZulu-Natal, due to the short survey period for information gathering and data collection. The COVID-19 pandemic also had a great impact on the undertaking of some key research processes mostly affecting the research methodology, particularly during data collection. This study is the first of its kind in South Africa to assess the maturity of provincial government departments to implement the IDMS, which is indicative of an evaluation void gap.